GMAS-1DMCSP: GENETIC MULTI-AGENT SYSTEM FOR SOLVING ONE-DIMENSIONAL CUTTING STOCK PROBLEM WITH MULTIPLE STOCK SIZES - Hoài Phương, Phan Thị; Mai, Lương Chi (Vietnam Journal of Science and Technology, 2012)
SUMMARY Multi-agent systems (MASs) as an emerging sub-field of  artificial intelligence concern with interaction of agents to solve a common problem. This paradigm has become more and more important in many aspects of computer science by introducing the issues of distributed intelligence and interaction. They represent a new way of analyzing, designing, and implementing complex software systems. This paper introduces a JADE-Based distributed Multi-agents system for solving One-Dimensional Cutting Stock Problem with Multiple Stock Sizes on the basis of the theoretical results presented in [1]. The system has effectively been operating in the industrial environment.